Neuromodulation: clinical advances and future perspectives - ZHANG Jian⁃guo; XIE Hu⁃tao; YANG An⁃chao (Chinese Journal of Contemporary Neurology and Neurosurgery, 2025)
With the rapid development of society and economy and the acceleration of population aging, the global disease spectrum has undergone profound changes. Neurological diseases, especially brain functional disorders, have become major threats to human health. Neuromodulation technique, as a critical means to address this challenge, has opened new avenues for the treatment of brain functional disorders and has become one of the three innovative technologies in modern neurosurgery. This paper systematically elaborates on the concept, classification, and technological evolution of neuromodulation, focusing on the clinical application progress of invasive neuromodulation technique. It analyzes their efficacy and potential in the fields of movement disorders, epilepsy, pain, cognitive impairment, and neurorehabilitation. Additionally, it explores the integration trend between neuromodulation and brain⁃computer interface (BCI), pointing out that closed⁃loop neuromodulation has become an important component of BCI, providing new approaches for precise treatment and individualized modulation. Finally, it proposes future development directions in the field of neuromodulation, including expanding new indications, innovating target exploration models, updating treatment concepts, and conducting high⁃quality evidence⁃based medical research. Looking ahead, Chinese neuromodulation endeavors should seize current opportunities, achieve a leap from following to leading through continuous exploration and innovation, and make greater contributions to global brain health.